Testing the Lipstick Effect: An Experimental Study of Women's Lifestyle and Financial Resilience in Maumere - Besli, Eugenius; Lamanepa, Angela Merici Paskaliamuis; Aprilianti, Anyela Paskalia (Dinasti Publisher, 2026)
This research aims to examine the lipstick effect phenomenon in relation to women’s lifestyle and financial resilience in Maumere City. Data were collected through questionnaires and case scenarios designed to align with the research objectives. The study population included women cosmetic users in Maumere City. Sampling employed a combination of simple random, purposive, and quota techniques. Simple random sampling was used to select respondents randomly, purposive sampling ensured participants met the research criteria, and quota sampling balanced the number of participants between experimental and control groups. Data were analyzed using Pearson correlation, paired sample t-test, and independent sample t-test. The paired sample t-test results showed a significance value (2-tailed) greater than 0.05, meaning no significant difference between pretest and posttest results in both groups. Similarly, the independent sample t-test showed no significant difference between the groups regarding consumptive lifestyle and weak financial resilience. However, the Pearson correlation test revealed a significance value (2-tailed) less than 0.05, demonstrating a strong relationship between a consumptive lifestyle and poor financial resilience. These findings confirm the presence of the lipstick effect among women in Maumere City, especially amid financial challenges and ineffective money management.